Ordered assemblies of peptide nanoparticles with only positive charge - Yi Shi; Tianren Zhang; Rui Guo; Zihan Zhang; Amanda L. McCahill; Yao Tang; Sabrina E. Liskey; Dai-Bei Yang; Christopher J. Kloxin; Jeffery G. Saven; Darrin J. Pochan (Nature Communications)
Abstract Surface charge patchiness of different charge types can influence the solution behaviours of colloidal particles and globular proteins. Herein, coiled-coil ‘bundlemer’ nanoparticles that display only a single type of surface charge (SC) are computationally designed to compare their solution behaviours to mixed charge-type (MC) counterparts with both positively and negatively charged side chains. Nematic and columnar liquid crystal phases are discovered in low concentrations of SC particles, indicative of particle end-to-end stacking into columns combined with lateral electrostatic repulsion between columns, while MC particles with the same net charge and particle shape produced only amorphous, soluble aggregates. Similarly, porous lattices are formed in mixtures of SC/MC particles of opposite charges while MC/MC mixtures of opposite charges produce only amorphous aggregates. The lattice structure is inferred with a machine learning optimization approach. The differences between SC and MC particle behaviours directly show the importance of surface electrostatic patchiness.